Cutaneous vasculitis as the sole manifestation of disseminated gonococcal infection: case report. Issue 2 (April 1994) - Mastrolonardo, M; Loconsole, F; Conte, A; Rantuccio, F
Abstract : One of the possible systemic complications of gonorrhoea is disseminated gonococcal infection (DGI), which is usually characterised by both skin and joint lesions. While joint involvement ranges from tenosynovitis to suppurative arthritis, cutaneous involvement features varied non-specific patterns often clinically and histologically consistent with vasculitis. We report a case of DGI in which an extensive, vesicobullous, haemorrhagic, and necrotic cutaneous vasculitis was the sole manifestation of the disease.